2009
DOI: 10.1063/1.3284379
|View full text |Cite
|
Sign up to set email alerts
|

Geometrizing the Quantum—A Toy Model

Abstract: It is shown that the equations of relativistic Bohmian mechanics for multiple bosonic particles have a dual description in terms of a classical theory of conformally "curved" space-time. This shows that it is possible to formulate quantum mechanics as a purely classical geometrical theory. The results are further generalized to interactions with an external electromagnetic field.PACS numbers: 04.62.+v, 03.65.Ta A. IntroductionIn standard quantum mechanics observables and the corresponding uncertainty are promo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…we find that the geometrical equation (18) is identical to the quantum equation (9). Please note that in relativistic case the dual theory was developed in 4n dimensions [19] while here equation (18) is obtained from the geometric theory developed in (1 + 3n) dimensions.…”
Section: The Equation Of Motion Formentioning
confidence: 91%
See 2 more Smart Citations
“…we find that the geometrical equation (18) is identical to the quantum equation (9). Please note that in relativistic case the dual theory was developed in 4n dimensions [19] while here equation (18) is obtained from the geometric theory developed in (1 + 3n) dimensions.…”
Section: The Equation Of Motion Formentioning
confidence: 91%
“…Using the language of [21,22], it was shown that such trajectories naturally arise in the configuration space for the complex Klein Gordon equation. It was further found that the evolution equation for those trajectories can be cast in the form of a geodesics equation in a conformally rescaled configuration space [2,3,7,9,18,19]. Thus, the relativistic Klein Gordon equation can be rewritten in a geometric language with non-trivial trajectories in configuration space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometric treatments of quantum mechanics have also been studied in depth; for a sample see, e.g. [2,[20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Thus it naturally led many physicists to the attempt to reformulate quantum mechanics in a geometric language, like GR. References [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] are a few such efforts towards the geometrical rewriting of quantum laws.…”
Section: Introductionmentioning
confidence: 99%